Improvements of storm surge forecasting in the Gulf of Venice exploiting the potential of satellite data: the ESA DUE eSurge-Venice project - Francesco De Biasio; Marco Bajo; Stefano Vignudelli; Georg Umgiesser; Stefano Zecchetto (European Journal of Remote Sensing, 2017)
The northern Adriatic Sea is affected by storm surges, which often cause the flooding in Venice and the surrounding areas. We present the results of the eSurge-Venice project, funded by the European Space Agency (ESA) in the framework of its Data User Element programme: the project was aimed to demonstrate the potential of satellite data in improving storm surge forecasting, with focus on the Gulf of Venice. The satellite data used were scatterometer wind and altimeter sea level height. Hindcast experiments were conducted to assess the sensitivity of a storm surge model to a model wind forcing modified with scatterometer data and to altimeter retrievals assimilated with a dual 4D-Var system. The modified model wind forcing alone was responsible for a reduction of the mean difference between modelled and observed maximum surge peaks from −15.1 to −8.2 cm, while combining together scatterometer and altimeter data the mean difference further reduced to −6.0 cm. In terms of percent, the improvements in the reduction on the mean differences between modelled and observed surge peaks reaches 46% using only the scatterometer data, and 60% using both scatterometer and altimeter data.